2016
DOI: 10.1021/jacs.6b05066
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Li-Ion Transport from Picoseconds to Seconds: Bulk versus Interfaces in an Argyrodite Li6PS5Cl–Li2S All-Solid-State Li-Ion Battery

Abstract: One of the main challenges of all-solid-state Li-ion batteries is the restricted power density due to the poor Li-ion transport between the electrodes via the electrolyte. However, to establish what diffusional process is the bottleneck for Li-ion transport requires the ability to distinguish the various processes. The present work investigates the Li-ion diffusion in argyrodite Li6PS5Cl, a promising electrolyte based on its high Li-ion conductivity, using a combination of (7)Li NMR experiments and DFT based m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
212
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 211 publications
(240 citation statements)
references
References 56 publications
19
212
1
1
Order By: Relevance
“…9), which probes the lithium-ion hopping through the bulk lattice, resulted in a conductivity of 0.013(1) S cm −1 at 78 °C with an activation energy of 0.10(5) eV, indicating mobility comparable with recently reported NMR results 51 , and a larger bulk conductivity than that resulting from impedance spectroscopy. This may indicate that, like for the analogous Li 6 PS 5 Cl, grain boundaries may be responsible for the lower bulk conductivity measured by impedance spectroscopy 24 .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…9), which probes the lithium-ion hopping through the bulk lattice, resulted in a conductivity of 0.013(1) S cm −1 at 78 °C with an activation energy of 0.10(5) eV, indicating mobility comparable with recently reported NMR results 51 , and a larger bulk conductivity than that resulting from impedance spectroscopy. This may indicate that, like for the analogous Li 6 PS 5 Cl, grain boundaries may be responsible for the lower bulk conductivity measured by impedance spectroscopy 24 .…”
Section: Resultsmentioning
confidence: 89%
“…In addition to the 2D exchange measurements, faster 1D 7 Li– 7 Li exchange experiments under static conditions were performed to quantify the exchange as a function of t mix and temperature 24, 47, 49 . The much larger static spectral width of 7 Li in Li 2 S compared to that of Li 6 PS 5 Br, see Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 To compare the intrinsic Li-ion mobility, temperature-dependent  7 Li spin–lattice relaxation rate (1/ T 1 ) measurements were performed for both BMA-Li 6 PS 5 Cl and SSM-Li 6 PS 5 Cl, the results of which are shown in Figure 5b. The temperature dependence of the 7 Li spin–lattice relaxation (SLR) rates in the laboratory frame can be used to quantify the Li-ion jump frequency and the corresponding energy barrier.…”
Section: Resultsmentioning
confidence: 99%
“…Using nuclear magnetic resonance spectroscopy, Yu et al reported that the electrolyteelectrode Li 6 PS 5 Cl-Li 2 S interface is the dominant factor responsible for the restricted power performance. 13 To improve the interfacial transfer, in addition to interlayer coatings, 14 Sharafi et al found that the interfacial resistance of Li-Li 7 La 3 Zr 2 O 12 can be dramatically reduced by controlling surface chemistry, which contributes to good cycling performance. 15 A mechanically robust and stable interface is also of great importance to all-solid-state Li-ion batteries.…”
mentioning
confidence: 99%